A Method of Model Experiments for Regularizing the Problem of Recovery of the Input Signal of the Linear Object by the Integral Dynamic Model - Sterten, Jo; Furtat, Yuriy Olegovich (Kamianets-Podilskyi National Ivan Ohiienko University, 2017)
The method of determining the parameter of regularization for solving the problem of restoring the input signal of a linear stationary object under the conditions of the existence of measurement errors and the process of solving is considered. The proposed method of model experiments allows to separate errors of different types and restore the real input signal